DNA barcoding of Vietnamese bent-toed geckos (Squamata: Gekkonidae: Cyrtodactylus) and the description of a new species - Nguyen, Sang Ngoc; Yang, Jun-Xiao; Le, Thanh-Ngan Thi; Nguyen, Luan Thanh; Orlov, Nikolai L.; Hoang, Chung Van; Nguyen, Truong Quang; Jin, Jie-Qiong; Rao, Ding-Qi; Hoang, Thao Ngoc; Che, Jing; Murphy, Robert W.; et al. (Zootaxa, 2014)
Species of bent-toed gecko (Cyrtodactylus) in Vietnam have been described at a rate of nearly four species per year since 2007 mostly based on morphological data. A tool that guides species delimitation will accelerate the rate of documentation, and at a time when the recognition of species greatly benefits conservation. We use DNA barcoding using COI (550 bp) to re-examine the levels of genetic divergence and taxonomic status of 21 described species of Vietnamese bent-toed geckos. Tree-based analyses resolve all sampled species and identify potential undescribed taxa. Kimura 2-parameter genetic distances between the described species average 21.0±4.2% and range from 4.3% to 28.7%. Further, our analyses discover two potentially new species from Vietnam, two from Laos and one from China. Herein we describe the new species Cyrtodactylus puhuensis sp. nov. from Vietnam on the basis of both genetics and morphology. Genetically, it differs from the remaining species by an average K2P distance of 24.0±1.8%. Morphologically, the new species is diagnosed by its medium-size (snout-vent length 79.24 mm and tail length 82.59 mm, for the single known individual), in having a series of moderately enlarged transverse subcaudals and a series of moderately enlarged femoral scales that extend from precloacal scales, in possessing femoral scales without pores, with males having five precloacal pores, and in exhibiting 8 supralabials, 10 infralabials, 23 narrow subdigital lamellae on its fourth toe, and 36 transverse ventrals.